ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI CAKUPAN PROGRAM ANTENATAL CARE BUMIL - Mudarmawati Mudarmawati (Universitas Prima Indonesia, 2022)
ANC or antenatal care is the care of the mother and fetus during pregnancy. Through ANC, various information and education related to pregnancy and preparation for delivery can be given to mothers as early as possible. This type of research is observational with a cross-sectional study design. The study was carried out at the Silih Nara Health Center, Central Aceh Regency in August 2021 from June to August 2021. The population in this study were all mothers who gave birth recorded as many as 65 people and all of them were used as samples (total sampling). The instrument used to collect study data is a developed questionnaire. The statistic test uses univariate, bivariate, and multivariate regression data analysis. The results were obtained: there was an effect on education, knowledge, attitude, family support, affordability of health facilities, and support of health workers while age and occupation had no effect on the coverage of the ANC program. The variable affordability of health facilities has the most dominant influence on the coverage of the ANC program. It is recommended for the puskesmas to increase the visits of pregnant women so that the Silih Nara Health Center further increases the knowledge of pregnant women through counseling about the importance of Antenatal Care.